External Financing and Financial Development in Developing Countries: Aggregate and Disaggregate Empirical Evidence from West Africa - Noah, Afees Oluwashina; Abdulmumini, Maryam Jumai; Rahji, Ibrahim Ohize; David, Oladipo Olalekan (ABUAD Journal of Social and Management Sciences, 2023)
External financing as one of the drivers of financial development remains a subject of ongoing debate. While some studies assert a positive influence, others dispute this claim. This study contributes to the existing studies on the subject matter, with the primary objective of examining the overall or aggregate effects of external financing on financial development. Specifically, the study examines the individual effects of external financing factors (FDI, ODA, and remittances) on financial development, both in the short and long run, by employing annual panel data spanning from 1980 to 2021 for the selected West African countries. To achieve this, the study employs the panel autoregressive distributed lag (PARDL) variants (mean group - MG, dynamic fixed effect - DFE, and pooled mean group - PMG) techniques. The results from the PMG and DFE estimations reveal that external financing as a whole has an impact on financial development in West African countries both in the long and short run. Remittance, economic growth, and inflation rate also have a significant influence on financial development both in the long and short run. While ODA is detrimental to financial development in the long run, FDI does not influence financial development. It is therefore imperative for stakeholders within the sub-region to encourage and facilitate the use of remittances, economic growth, and inflation rate as means of promoting financial development in West Africa, while simultaneously ensuring that FDI and ODA are used to promote self-sufficiency and financial stability and align with the region’s developmental goals.